BENCHMARK STUDY ON THE SPECIES AREA CURVE OF MOUNT LANTOY, ARGAO, CEBU - Lillo, EP; Alcazar, SMT; Malaki, AB; Alburo, HM; Agbay, EA; Rica, RLV; Manalastas, RDC; Obiso, LS; Hoyohoy, GB; Opiniano, RP (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
The study aimed to know the species area curve relationship in Mount Lantoy as well as the species composition, species diversity and relative abundance. Data collection and analysis were conducted through species area curve method. Result shows high species diversity observed. Likewise the plots established in the lower have more species composition compared to middle and upper slope. Most of them were dicot species. The 8 x 16 meters plots size was found to be the most suited in conducting sampling inventory in mount lantoy. Mount Lantoy has a total of 120 species which include 68 families, and 81 genera. Out of the total species 88 of them were dicot, 9 species were monocot and 23 species were ferns and allies. Five endangered species based from DENR (2007) national list were found in the area. Protection and conservation of the species in mount lantoy was necessary.